Long Time Behavior of the Modified One-Dimensional Derivative Schrödinger Equation (Analysis in Theory and Applications, 2026)
We study the long time behavior of the modified one-dimensional deriva- tive Schrödinger equation $(D_t - F(D))u = D_x(|u|^2u)$, where $F(ξ)$ is a nonnegative second order constant coefficient elliptic symbol. For any smooth initial datum of size $ε \ll 1$, we prove that the solution is global-in-time, combining the vector fields method and a semiclassical analysis method introduced by Delort. Moreover, we present the pointwise decay estimates and the large time asymptotic formulas of the solution.
Keywords: Derivative Schrödinger Equation; semiclassical analysis; large time asymptotics